Student’s Perception in Using Online Listening Media in Improving Listening Skills at Junior High School - Alfina Safitri; Alief Noor Farida (Universitas Islam Negeri Palopo, 2026)
This research aimed to investigate the junior high school students’ perceptions on the use of online listening media in improving their listening skills based on the Technology Acceptance Model (TAM). The study focused on three indicators; Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioral Intention to Use (BI). This research used a descriptive quantitative design where the data was gathered using a questionnaire as the main instrument. The population of this study consisted of ninth-grade, with 64 students as the sample. The data were analyzed using descriptive statistics in the form of frequencies and percentages. According to the results of the questionnaire, the conclusion is students demonstrated positive perception of the use of online listening media for English learning. Students also showed positive perceptions regarding usefulness, ease of use, and the intention to continue using online listening media. These findings indicate that online listening media such as YouTube and podcasts can support students’ listening comprehension, enhance learning effectiveness, and encourage independent learning, but also promote learner engagement and independent learning among junior high school EFL learners. Furthermore, the positive responses indicate that technology-assisted listening activities have the potential to increase students’ motivation and acceptance of digital learning media in English language learning contexts. This study is important because junior high school students are still developing their English listening abilities and require appropriate technological support to improve engagement and comprehension in language learning.